Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2011)
We have, in India, today, about 2000 Engineering Colleges spread across the country along with a Faculty strength of more that 2,50,000. The AICTE is, still, liberally permitting the setting up of new Engineering colleges, every year.